An exploration and description of rural rehabilitation service model in the Mbhashe Municipality, Amathole district in the Eastern Cape Province of South Africa : a pilot study - Gysman, Nozipiwo Joyce (Stellenbosch : Stellenbosch University, 2020)
Thesis (MHumanRehabSt)--Stellenbosch University, 2020.